Maus : a survivor's tale - Spiegelman, Art (Pantheon Books, 1986)
A memoir about Vladek Spiegleman, a Jewish survivor of Hitler's Europe, and about his son, a cartoonist who tries to come to terms with his father, his story, and with history itself. Cartoon format portrays Jews as mice and Nazis as cats.